Challenges for Western Balkan Countries Regional Integration: the Case of North Macedonia - Toshevska-Trpchevska, Katerina; Disoska, Elena Makrevska; Kikerkova, Irena; Tonovska, Jasna (European Scientific Journal, ESJ, 2022)
This paper aims to elaborate on the possibilities that increased regional integration initiatives can have in boosting mutual trade among the countries in the Western Balkans region, such as: creating a Regional Economic Area by 2023; the creation of a Common Regional Market based on EU rules in the period 2021-2024 and the initiative “Open Balkan” created between North Macedonia, Serbia, and Albania for enabling free movement of goods and free movement of workers. For our research, the gravity model of trade for North Macedonia covering the period 2005-2020 is applied. The influence of bilateral and regional trade agreements on the country’s trade is analyzed. The results have shown that for North Macedonia, CEFTA-2006 membership has higher significance for increasing trade when compared to the agreement signed with the EU and to the other bilateral free trade agreements signed with EFTA, Turkey, and Ukraine. This paper point out that deepening trade integration through different regional initiatives could have a positive influence on increasing mutual trade.